A Systematic Literature Review on the Impact of EFL Classroom- Based Language Assessment - Fitriyah, Ima; Widiati, Utami (Soegijapranata Catholic University, 2021)
The trend in investigating how teachers apply assessment in EFL classroom has been at the momentum. Using systematic literature review and PRISMA protocol, as many as 44 research articles during this past ten years were found. Their findings are beneficial for EFL learning. Research investigating students' perceptions of Classroom-Based Language Assessment (CBLA) shows that students tend to have positive perceptions of CBLA. On another topic, students' motivation to implement CBLA depends on how the test itself is carried out. Few studies states that CBLA contributes greatly to students’ achievement, what is there is that they learn a lot from CBLA, and they sufficiently understand CBLA's function for learning. From the EFL teachers’ perspective, assessment literacy is crucial for them because at least 75% of research is found to focus on the application of assessment literacy, and the practice of assessment is one-way and balanced. This article discusses on how researchers have been using CBLA benefited for EFL teaching and learning.